ANALISIS PERAN MEDIA PEMBELAJARAN AUDIO VISUAL PADA SISWA SEKOLAH DASAR - Sa’diyah, Siti Halimatus; Sholihah, Ica Rif’atus; Zulfa, Risma Fitriya; Albahri, Muhammad Habibillah; SulthoniyahSulthoniyah, Luluk (Universitas Tanjungpura, 2023)
Learning method media visual audio is one of the methods that is currently used frequently, on the various teaching systems in school. There had many studies that have been done to find out the increase in student learning outcomes after this method was applied purpose of this study was done to look for how large the increase was by conducting Meta analysis techniques, while for the data collection method itself researchers using library studies methods that can go through several existing journal articles on the internet through the google scholar platforms with through several variable criteria needed as research material. After doing the research getting results on how the role of using audio visual media learning methods in elementary school students is a test resulting rate using the effect size cohen formula shows an increase included in the big category. However, because the subjects taken are also varied, the results of this test have not been able to become an indicator of how much the impact of this learning method because there are still many factors that affect the quality of learning supporting equipment, and also the level of teaching staff in each school on this method and also different.